Classification of Contracts in Sharia Business Law - Siregar, Ansor Syaputra (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2024)
Islamic law is a law that lives and continues to develop, has a very important role to answer questions in various matters, especially those related to contracts and agreements when entering into a contract. In making contracts, mistakes often occur in making names and the purpose of the contract so that mistakes often occur between the name and the substance of the contract. So to align the name and the substance of the contract, it is necessary to study the classification of a contract and the categorization of a contract when viewed from various aspects. The method of this research is in the form of literature study research (library research) with a descriptive analytic approach method. The results of this study are that there are many types of contract classifications from various aspects, but there are ten of the most well-known contract classifications, namely contract based on name, contract based on position, contract based on tempo, contract based on formality, contract based on syarak, contract based on validity, contract based on attachment, contract based on enforceability, contract based on dependents and contract based on objectives